Associations between physical activity intensity and motor balance in elementary school students: A sequential explanatory mixed-methods study - Firdaus, Fahrurrohman; Safari, Indra; Fauzi, Rizal Ahmad (Physical Education and Sports: Studies and Research, 2026)
Background: Children in primary school are becoming more sedentary due to advances in digital technology, which may reduce their physical activity levels. The development of motor skills, especially balance, which is an essential feature of children’s motor abilities, can be impacted by a lack of physical activity. Objectives: This study aimed to examine the association between physical activity intensity and motor balance in elementary school students. Methods: This study used a sequential explanatory mixed-methods design. The quantitative phase involved 50 students selected using saturated sampling, while the qualitative phase involved teachers and students selected purposively. Physical activity intensity was measured using the Physical Activity Questionnaire for Older Children (PAQ-C), while motor balance was assessed using the Balance Beam Test. Quantitative data were analyzed using Spearman’s rank correlation, and qualitative data were analyzed using thematic analysis in NVivo. Results: With a correlation coefficient of r = 0.687 and p < 0.05, the analysis demonstrated a strong, substantial positive link between motor balance levels and physical activity intensity. The intensity of physical activity accounted for 47.2% of motor balance. Qualitative research revealed that students with high levels of physical activity were more likely to engage in active play, such as running outside, cycling, and soccer, which, in turn, indirectly improve balance and postural stability. Conclusions: This study demonstrates that physical activity intensity plays an important role in the development of motor balance among elementary school students. These findings highlight the importance of integrating active movement-based learning strategies in physical education programs.